Coding of Non-coding RNA: Insights Into the Regulatory Functions of Pri-MicroRNA-Encoded Peptides in Plants - Ren, Yi; Song, Yue; Zhang, Lipeng; Guo, Dinghan; He, Juan; Wang, Lei; Song, Shiren; Xu, Wenping; Zhang, Caixi; Lers, Amnon; Ma, Chao; Wang, Shiping (Frontiers in Plant Science, 2021)
Peptides composed of a short chain of amino acids can play significant roles in plant growth, development, and stress responses. Most of these functional peptides are derived by either processing precursor proteins or direct translation of small open reading frames present in the genome and sometimes located in the untranslated region sequence of a messenger RNA. Generally, canonical peptides serve as local signal molecules mediating short- or long-distance intercellular communication. Also, they are commonly used as ligands perceived by an associated receptor, triggering cellular signaling transduction. In recent years, increasing pieces of evidence from studies in both plants and animals have revealed that peptides are also encoded by RNAs currently defined as non-coding RNAs (ncRNAs), including long ncRNAs, circular RNAs, and primary microRNAs. Primary microRNAs (miRNAs) have been reported to encode regulatory peptides in Arabidopsis, grapevine, soybean, and Medicago, called miRNA-encoded peptides (miPEPs). Remarkably, overexpression or exogenous applications of miPEPs specifically increase the expression level of their corresponding miRNAs by enhancing the transcription of the MIRNA (MIR) genes. Here, we first outline the current knowledge regarding the coding of putative ncRNAs. Notably, we review in detail the limited studies available regarding the translation of miPEPs and their relevant regulatory mechanisms. Furthermore, we discuss the potential cellular and molecular mechanisms in which miPEPs might be involved in plants and raise problems that needed to be solved.